Knowledge based system for the optimization of workplace design - Yin, Xingyan. (2008)
Appropriate workplace design is an effective way to prevent occupational musculoskeletal disorders. Workplace design is a data-intensive and multi-objective process. The problem of workplace design involves an unstructured and complex decision making process typically involving the use of domain dependent knowledge. However, there is a lack of effective design and evaluation tools for those without a strong ergonomic knowledge.